1996
DOI: 10.1103/physrevb.54.9730
|View full text |Cite|
|
Sign up to set email alerts
|

Capillary-wave roughening of surface-induced layering in liquid gallium

Abstract: The temperature dependence of surface-induced atomic layering in liquid gallium has been investigated with x-ray reflectivity. The prominent layering peak at q z ϭ2.4 Å Ϫ1 decreases dramatically upon heating from 22 to 170°C, but its width stays, unexpectedly, unchanged. The decrease is traced to the temperature dependence of capillary-wave induced surface roughness. The constant width indicates a temperature-independent layering decay length. The measured layering amplitudes are found to be significantly unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
74
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(82 citation statements)
references
References 21 publications
8
74
0
Order By: Relevance
“…In addition to the quasi-Bragg peak due to layering, XRR of the liquid Hg-air interface exhibits an anomalous intensity dip at lower scattering vectors and the surface roughness is found to grow with temperature faster than the prediction of CW theory [16], which describes well the thermal behavior of the liquid metal-air interface of Ga [17] and of all other liquid metals studied to date [18]. The Hgelectrolyte interface also exhibits anomalies.…”
Section: Introductionmentioning
confidence: 94%
“…In addition to the quasi-Bragg peak due to layering, XRR of the liquid Hg-air interface exhibits an anomalous intensity dip at lower scattering vectors and the surface roughness is found to grow with temperature faster than the prediction of CW theory [16], which describes well the thermal behavior of the liquid metal-air interface of Ga [17] and of all other liquid metals studied to date [18]. The Hgelectrolyte interface also exhibits anomalies.…”
Section: Introductionmentioning
confidence: 94%
“…This is so because the spatial density of surface electrons varies rapidly on the scale ∼ k −1 F as the Fermi wavelength k F is T-independent. By contrast, the amplitude of the first peak in the electronic density ρ(z) is temperature sensitive, at least over T-range from 30 to 200 • C [15]. According to Samojlovich's analysis [12] we associate the appearance of this maximum with the strength of surface electric field that should decrease on heating as the layering amplitude does [15,11].…”
Section: Theoretical Estimates Of ∆Smentioning
confidence: 99%
“…Theoretical studies of the liquid-vapor interfaces of pure metals and binary alloys (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13) lead to the following predictions: (i) the (longitudinal) distribution of density along the normal to the interface is stratified for several atomic diameters into the bulk liquid, and (ii) the species in excess in the liquid-vapor interface of a dilute binary alloy forms a monolayer that is the outermost layer of that interface. Recent x-ray reflectivity (XR) and grazing incidence x-ray diffraction (GIXD) studies of the liquidvapor interfaces of several pure metals and binary alloys have confirmed these predictions (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). In this paper, we report the results of XR and GIXD studies of the liquid-vapor interface of a dilute alloy of Pb in Ga over the temperature range of 23-76°C.…”
mentioning
confidence: 65%